An algebra problem by Wildan Bagus Wicaksono

Algebra Level 3

2017 x 2 + 4034 x + 17 + 2017 x 2 + 4034 x 3 = 10 \large \sqrt { { 2017x }^{ 2 }+4034x+17 } +\sqrt { { 2017x }^{ 2 }+4034x-3 } =10

Given the above, determine the value of x 2 + 2 x { x }^{ 2 }+2x .

11 2018 \frac { 11 }{ 2018 } 19 2017 \frac { 19 }{ 2017 } 11 2017 \frac { 11 }{ 2017 } 18 2017 \frac { 18 }{ 2017 } 13 2016 \frac { 13 }{ 2016 }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Oct 22, 2017

2017 x 2 + 4034 x + 17 + 2017 x 2 + 4034 x 3 = 10 Let u = 2017 x 2 + 4034 x + 7 u + 10 + u 10 = 10 Squaring both sides. u + 10 + 2 u 2 100 + u 10 = 100 2 u 2 100 = 100 2 u u 2 100 = 50 u Squaring both sides. u 2 100 = u 2 100 u + 2500 u = 26 2017 x 2 + 4034 x + 7 = 26 2017 x 2 + 4034 x = 19 x 2 + 2 x = 19 2017 \begin{aligned} \sqrt{2017x^2+4034x+17} + \sqrt{2017x^2+4034x-3} & = 10 & \small \color{#3D99F6} \text{Let }u = 2017x^2 + 4034x + 7 \\ \sqrt{u+10} + \sqrt{u-10} & = 10 & \small \color{#3D99F6} \text{Squaring both sides.} \\ u+10 + 2\sqrt{u^2-100} + u - 10 & = 100 \\ 2\sqrt{u^2-100} & = 100 - 2u \\ \sqrt{u^2-100} & = 50 - u & \small \color{#3D99F6} \text{Squaring both sides.} \\ u^2 - 100 & = u^2 - 100u + 2500 \\ u & = 26 \\ \implies 2017x^2 + 4034x + 7 & = 26 \\ 2017x^2 + 4034x & = 19 \\ \implies x^2 + 2x & = \boxed{\dfrac {19}{2017}} \end{aligned}

Interesting way of solving it!

Chua Hsuan - 3 years, 7 months ago

Log in to reply

Yes, I always look for interesting way.

Chew-Seong Cheong - 3 years, 7 months ago

2017 x 2 + 4034 x + 17 = p 2017 x 2 + 4034 x 3 = q \large \sqrt { 2017{ x }^{ 2 }+4034x+17 } =p\\ \large \sqrt { 2017{ x }^{ 2 }+4034x-3 } =q

So, p + q = 10 p+q=10

10 ( p q ) = ( p + q ) ( p q ) 10 ( p q ) = p 2 q 2 10 ( p q ) = ( 2017 x 2 + 4034 x + 17 ) 2 ( 2017 x 2 + 4034 x 3 ) 2 10 ( p q ) = 2017 x 2 + 4034 x + 17 ( 2017 x 2 + 4034 x 3 ) 10 ( p q ) = 2017 x 2 + 4034 x + 17 2017 x 2 4034 x + 3 10 ( p q ) = 20 p q = 2 \large 10(p-q)=(p+q)(p-q)\\ \large 10(p-q)={ p }^{ 2 }-{ q }^{ 2 }\\ \large 10(p-q)={ \left( \sqrt { 2017{ x }^{ 2 }+4034x+17 } \right) }^{ 2 }-{ \left( \sqrt { 2017{ x }^{ 2 }+4034x-3 } \right) }^{ 2 }\\ \large 10(p-q)=2017{ x }^{ 2 }+4034x+17-(2017{ x }^{ 2 }+4034x-3)\\ \large 10(p-q)=2017{ x }^{ 2 }+4034x+17-{ 2017x }^{ 2 }-4034x+3\\ \large10(p-q)=20\\ p-q=2

p + q = 10 p q = 2 + 2 p = 12 p = 6 \large p+q=10\\ \large p-q=2\\ -------+\\ \large 2p=12\\ \large p=6

So we get,

p = 6 2017 x 2 + 4034 x + 17 = 6 2017 x 2 + 4034 x + 17 = 36 2017 ( x 2 + 2 x ) = 36 17 2017 ( x 2 + 2 x ) = 19 x 2 + 2 x = 19 2017 \large p=6\\ \large \sqrt { 2017{ x }^{ 2 }+4034x+17 } =6\\ \large 2017{ x }^{ 2 }+4034x+17=36\\ \large 2017({ x }^{ 2 }+2x)=36-17\\ \large 2017({ x }^{ 2 }+2x)=19\\ \large { x }^{ 2 }+2x=\frac { 19 }{ 2017 }

Chua Hsuan
Oct 29, 2017

2017 x 2 + 4034 x + 17 + 2017 x 2 + 4034 x 3 = 10 \sqrt{2017x^2+4034x+17}+\sqrt {2017x^2+4034x-3}=10

2017 ( x 2 + 2 x ) + 17 + 2017 ( x 2 + 2 x ) 3 = 10 \sqrt{2017(x^2+2x)+17}+\sqrt{2017 (x^2+2x)-3}=10

2017 ( x 2 + 2 x ) + 17 = A , 2017 ( x 2 + 2 x ) 3 = B \sqrt{2017(x^2+2x)+17}=A,\sqrt{2017 (x^2+2x)-3}=B

Keeping in mind that , A + B = 10 \text{Keeping in mind that},A+B=10

A 2 B 2 = 10 ( A B ) A^2-B^2=10(A-B)

( 2017 ( x 2 + 2 x ) + 17 ) 2 ( 2017 ( x 2 + 2 x ) 3 ) 2 = 10 ( 2017 ( x 2 + 2 x ) + 17 2017 ( x 2 + 2 x ) 3 ) \therefore (\sqrt{2017(x^2+2x)+17})^2-(\sqrt {2017 (x^2+2x)-3})^2=10(\sqrt{2017(x^2+2x)+17}-\sqrt {2017 (x^2+2x)-3})

2017 ( x 2 + 2 x ) + 17 2017 ( x 2 + 2 x ) + 3 = 10 ( 2017 ( x 2 + 2 x ) 2017 ( x 2 + 2 x ) 3 ) \therefore 2017 (x^2+2x)+17-2017 (x^2+2x)+3=10 (\sqrt {2017 (x^2+2x)}-\sqrt {2017 (x^2+2x)-3})

20 = 10 ( A B ) \therefore 20=10 (A-B)

A B = 2 \therefore A-B=2

Since A+B=10 and A-B=2, A=6 and B=4 \text{Since A+B=10 and A-B=2, A=6 and B=4}

2017 ( x 2 + 2 x ) + 17 = A = 6 \therefore \sqrt {2017 (x^2+2x)+17}=A=6

2017 ( x 2 + 2 x ) + 17 = 36 \therefore 2017 (x^2+2x)+17=36

2017 ( x 2 + 2 x ) = 19 \therefore 2017 (x^2+2x)=19

x 2 + 2 x = 19 2017 \therefore x^2+2x=\frac {19}{2017}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...